The Impact of Immune Interaction on the Metastatic Infiltration of Colorectal Carcinoma to Lymph Nodes - Vycital, Ondrej; Dubova, Magdalena; Palek, Richard; Hosek, Petr; Branzovsky, Jindrich; Treska, Vladislav; Daum, Ondrej; Liska, Vaclav (Anticancer research, 2018)
BACKGROUND/AIM: Tumour-infiltrating lymphocytes (TILs) and Granzyme B play crucial roles in immune reactions against colorectal carcinoma (CRCa). The inhibitor of Granzyme B is Serpin B9. The aim of this study was to evaluate the effect of immunohistological parameters of TILs on the prognosis of CRCa and presence of lymph node metastasis. PATIENTS AND METHODS: A total of 152 patients who underwent surgery for CRCa were analyzed, including 63 patients in cohort stage II, according to the Union for International Cancer Control (UICC), and 89 patients in cohort UICC stage III. The TIL pattern was classified as peritumoural (PTL), intratumoural (ITL), intrastromal (ISL) or Crohn-like, and immunohistological staining of TIL and cancer cells was also performed. RESULTS: A significantly higher density of CD8+ and CD4+ TILs was observed in the UICC II group, and significantly higher densities of CD4+ TILs were observed in the UICC II group in all distinguished patterns. In the same cohort, higher numbers of CD57+ cells and FoxP3+ TILs and Granzyme B levels were observed. In cohort UICC III, there was a higher density of ISL, PTL CD8+, CD25+ TILs and cancer cells showed staining for Serpin B9. CD57, Granzyme B and CD8 were demonstrated as positive prognostic factors of overall survival, and CD57 and CD4+ TILs were demonstrated as positive prognostic factors of recurrence. CONCLUSION: TILs and CD57 are promising prognostic factors of CRCa. The association of Serpin B9 with lymph node metastasis reveals a potential mechanism for tumour resistance to immune reaction.
Keywords: FoxP3; CD25; Humans; tumour-infiltrating lymphocytes; Biomarkers, Tumor; Female; Aged; Serpin B9; senioři; lidé; CD4; Lymphatic Metastasis; Lymphocytes, Tumor-Infiltrating; lymfatické metastázy; nádorové biomarkery; lymph node metastasis; ženské pohlaví; CD56; kolorektální nádory; Male; CD57; CD8; recurrence; natural killer cells; tumor infiltrující lymfocyty; Aged, 80 and over; Colorectal carcinoma; senioři nad 80 let; mužské pohlaví; Colorectal Neoplasms